Professional collaboration in lesson studies in the perspective of participants teachers - Richit, Adriana [UNESP]; Da Ponte, João Pedro (FapUNIFESP (SciELO), 2019)
This paper analyses teacher collaboration in lesson studies, regarded as a professional development process. We interviewed seven teachers, from the 1st to the 3rd cycle of basic education, who participated in three lesson studies carried out in public schools in Lisbon, in 2013-2014, led by a team of researchers from the Instituto de Educação da Universidade de Lisboa. The interviews were semi-structured and were undertaken in June and July of 2016, being analyzed in the qualitative and interpretative research perspective. The results suggest that in the context of a lesson study, collaboration among teachers takes place in the intersection of three main aspects - sharing, cooperating, and personal stimulus - and show up especially in planning and carrying out the research lesson and in the daily professional activities.
A colaboração profissional em estudos de aula na perspectiva de professores participantes
Keywords: Lesson Studies; Professional Collaboration; Teacher Professional Development